Novas diretrizes para a seleção granulométrica de misturas asfálticas densas com foco na deformação permanente - Ferreira, Jorge Luis Santos (2017)
The permanent deformation in flexible pavements is a distress that typically manifests at early ages and mainly occurs in the asphalt layer. Although several factors are associated with this kind of failure, the literature emphasizes that the grain size distribution plays an essential role, because it makes up the resistant skeleton. Despite its relevance, the role of gradation is superficially considered in the asphalt mixtures design. This work focuses on the proposition of a simple method to evaluate the quality of the grain size distribution and its potential to form rutting resistant asphalt mixtures. This method is based on the hypothesis of the existence of a main aggregate structure responsible for absorbing and transmitting stresses without developing plastic deformation in the asphalt mixture. Two parameters were proposed to characterize this structure, denominated α and G ratios. The first one characterizes the degree of interlocking, while the second one is related to the sizes of particles. The result of the uniaxial repeated load test (Flow Number, FN) was adopted to indicate the rutting susceptibility of asphalt mixtures. Both parameters were shown to be correlated with FN, characterizing them as useful tools to assist the composition of resistant gradations. In comparison to the parameters of the Bailey method, the parameters now suggested had better correlations with the FN. Moreover, the analysis by Digital Image Processing of the internal structure of some asphalt mixtures showed the ability of the α ratio to estimate interlocking of mineral skeleton. After, the κ index was established, conceived as a characteristic parameter of the asphalt mixture that indicates the rutting resistance. This index is obtained by a non-linear combination of the gradation parameters (α and G) and the viscosity of the asphalt binder used in the asphalt mixture. An excellent correlation was observed between the FN and the κ index. Finally, criteria for the κ index were suggested as a function of traffic level. Thus, it is expected that this work has contributed to the development of rational methods that subsidize the choice of resistant and stable gradation compositions for better quality pavements. Key words: Permanent deformation. Gradation. Asphalt mix. Flow